Peran Sekolah Perempuan dalam Memperkuat Fungsi Keluarga bagi Ibu Rumah Tangga di Desa Tanjung Rejo - Ndraha, Ewi Darman; Nainggolan, Elizon (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2024)
This research aims to determine the Role of Women's Schools in Strengthening the Family Function in the Educational Field for Housewives in Tanjung Rejo Village. This research was conducted at PKBM Laskar Pelangi as the venue for women's school activities in Tanjung Rejo Village, Percut Sei Tuan sub-district. The type of research used is qualitative descriptive research. The subjects in this study are 2 managers of women's schools and 2 learning participants. Data collection techniques used are observation, interviews, and documentation. Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. The technique for checking the validity of data includes credibility testing, dependability testing, transferability testing, and confirmability testing. The results of the study show several findings: 1) Women's schools contribute positively to instilling religious education, introducing values such as patience, honesty, and sex education, creating an environment that supports the spiritual and moral development of learning participants. 2) The role of women's schools in moral education contributes positively by integrating moral values into the curriculum. 3) Women's schools help families create a safe emotional environment, supporting children in dealing with feelings and emotions. 4) The role of women's schools in developing household skills provides practical knowledge and training related to managing daily household tasks. 5) Women's schools successfully develop vocational skills, such as utilizing social media, making accessories, and entrepreneurial skills, contributing to the ability of housewives to apply these skills in daily life and even encouraging the opening of small businesses at home. Keywords: Role of sekolah perempuan, Family function, Housewives